Comparative study on dog bite and rabies in livestock and pet animal with their management in Faridpur sadar upazilla Veterinary hospital - Rumi, Md Aftabuddin; Bari, Md Saiful; Abid, Md Harisul; Rabbani, Golam; Hossain, Mohammad Belayet (Research in Agriculture Livestock and Fisheries, 2018)
A cross-sectional study was carried out from 13th January to 15thMarch 2015 in the Upazilla Veterinary Hospital of the Sadar Upazilla under Faridpur District to estimate the dog bites, rabies, and their management in different livestock and pet animals registered for treatment. A prototype questionnaire was used to obtain the necessary information from the owners of the animals observed. Out of the total 170 animals diagnosed and treated based on gross lesion and history, 24, 13, 133 were cattle, dogs, and goats, respectively. The proportion positive of dog bite cases was 17.4% in cattle, 20.5% in goats, and 8.3% in dogs. Among the dog bitten animals, 77.8% were Category-III (single or multiple transdermal bites or scratches, licks on broken skin) bite. The prevalence of rabies in dog bitten animals was 2.50% in dogs, 0.8% in goats and no rabies case was recorded in cattle. Post-rabies vaccine was used in 46.4%, 100% and 75.0% dog-bitten goats, cattle and dogs, respectively. The occupation and literacy of the owner, types of cattle, animal’s age, and animal source etc. showed a considerable difference in prevalence. However, none of the association was statistically significant. This baseline study might be extended with a required number of samples to identify potential risk factors for the occurrence of rabies in different animals. Res. Agric., Livest. Fish.5(2): 215-224, August 2018